Identification of Coronary Morphological Damage in Patients with Chronic Inflammatory Rheumatic Diseases - Elena Heras-Recuero; Juan Antonio Martínez-López; Macarena Garbayo-Bugeda; Álvaro Castrillo-Capilla; Teresa Blázquez-Sánchez; Arantxa Torres-Roselló; Antia García-Fernández; Javier Llorca; Raquel Largo; Juan Antonio Franco-Peláez; José Tuñón; Miguel Ángel González-Gay (Diagnostics)
Objective: Patients with chronic inflammatory rheumatic diseases (CIRDs) have a higher incidence of coronary artery disease (CAD) due to accelerated atherogenesis. This study aimed to assess the extent and location of CAD lesions in CIRD patients compared to non-CIRD patients. Methods: A retrospective study was conducted on CIRD patients (rheumatoid arthritis, ankylosing spondylitis, and psoriatic arthritis) who underwent coronary angiography at Hospital Fundación Jiménez Díaz (Madrid, Spain) between 2018 and 2022. For each CIRD patient, at least two frequency-matched controls were selected based on sex, age (±2 years), diabetic status, and clinical indication for coronary angiography. The indications for coronary angiography in both groups were chronic coronary syndrome and acute coronary syndrome with or without ST elevation. Results: A total of 66 CIRD patients were included, with 42 (63.6%) women, and a median age of 66.6 years (range: 58.3–75.2). Compared to the controls, CIRD patients had a higher number of affected coronary arteries (2.03 vs. 1.56, p = 0.03). The mid-anterior descending artery and the right posterior descending artery were more frequently involved in CIRD patients than in controls (odds ratio [OR] of 2.45 and 3.53, respectively, p ≤ 0.02 for both comparisons). The frequency of coronary calcification was higher in CIRD patients, though the difference did not reach statistical significance (5 of 66 in CIRD patients vs. 3 of 140 in non-CIRD controls, OR of 3.74, p = 0.06). Revascularization was more commonly performed in patients with CIRD (50 of 66 vs. 85 of 140 in those without CIRD (OR: 2.02 [95% CI: 1.01–4.18]; p = 0.03). Conclusions: Patients with CIRD exhibit more extensive CAD, with a higher propensity for involvement inthe mid-anterior descending and right posterior descending arteries compared to patients without CIRD. These findings highlight the need for closer cardiovascular monitoring and early risk stratification in CIRD patients to improve the detection and management of CAD.